1981
DOI: 10.1136/bmj.282.6266.771
|View full text |Cite
|
Sign up to set email alerts
|

Patient-controlled dose regimen of methadone for chronic cancer pain.

Abstract: Fourteen patients with severe cancer pain participated in a trial of methadone given in a fixed dose (10 mg) but at intervals selected by the patients themselves during the loading phase. The aim was to achieve rapid pain relief while avoiding the risk of toxicity from accumulation of methadone. As expected, the dosage intervals increased gradually over the first few days of treatment, the daily dose decreasing from 30-80 mg on the first day to 10-40 mg at the end of the week. Plasma concentrations of methadon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0

Year Published

1989
1989
2013
2013

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(18 citation statements)
references
References 9 publications
1
17
0
Order By: Relevance
“…Fredheim et al reported that morphine and metabolites were completely eliminated and steady state for methadone reached within 1 week in 12 patients with nonmalignant pain after a 3DS [17]. Only one study describes plasma concentrations of methadone after a switch from oxycodone in cancer patients [19]. The switching strategy in that study was patient controlled, and methadone concentrations were at steady state after 2-3 days.…”
Section: Introductionmentioning
confidence: 96%
“…Fredheim et al reported that morphine and metabolites were completely eliminated and steady state for methadone reached within 1 week in 12 patients with nonmalignant pain after a 3DS [17]. Only one study describes plasma concentrations of methadone after a switch from oxycodone in cancer patients [19]. The switching strategy in that study was patient controlled, and methadone concentrations were at steady state after 2-3 days.…”
Section: Introductionmentioning
confidence: 96%
“…More comprehensive data on methadone kinetics have been collected from other clinical groups including cancer patients receiving i.v. infusions of methadone (5-40 mg ) for the relief of chronic Drug administration pain [16][17][18][19][20], and surgical patients given parenteral metha-…”
mentioning
confidence: 99%
“…The pharmacokinetics in non-tolerant ("naive") subjects might differ from those in tolerant subjects [10,11]. Also short-term treatment might give different results from long-term (steady-state) treatment [12,13]. However, it seems that determinations of plasma methadone in outdoor addicts show wider scatters in elimination half-lifes than those performed in closed metabolic wards: 17.8-63.8 h [8] and 18.9-43 h [2], respectively.…”
mentioning
confidence: 99%